Termite associated to oil palm stands in three types of soils in Ladang Endau Rompin, Pahang, Malaysia - Nur-Atiqah Jalaludin,; Faszly Rahim,; Salmah Yaakop, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Termites are found in various habitats, particularly diverse communities occurring in tropical forest and peatlands. Termites are beneficial insects, which function as soil engineers, improving the soil quality. However, in peatlands converted to commercial oil palm plantations, they are considered as pests. There is lack of studies on termite communities in converted peatlands in Peninsular Malaysia. Thus, this study investigated termite species associated with oil palm stands in three soil types (clay, shallow peat and deep peat) in Endau Rompin Plantation. The stand scouting method was used to record the numbers and types of termites associated with palm trees in the individual stands on different soil types. A total of 29 termite species associated with the palm stands were identified morphologically. All the species belonged to the families Rhinotermitidae and Termitidae. Twenty-three of the 29 species were found in the shallow peat, 16 in clay soil and 15 in deep peat. The community structure was synthesized by two-way cluster analysis with Sorensen (Bray Curtis) distance measure. Five termite groups associated with two soil types (clay soil and shallow/deep peat) were generated. Moisture levels and organic content were likely to determine the presence of soil feeders identified in the presence study. This study provides information on the status of termite species in oil palm plantation areas. Such information may be useful in future planning strategies by the plantation management.